MAQASID SYARIAH SEBAGAI FILSAFAT HUKUMISLAM: Sebuah Pendekatan Sistem Menurut Jasser Auda - Maulidi, Maulidi (Al-Mazaahib: Jurnal Perbandingan Hukum, 2015)
The ushul fikih thought had stagnated during this time, because it was built from the deductive way of thinking and using the paradigm of which is identical with the positivistic schools. Islamic law  is derived from the text (nash) through the analysis of linguists an sich. But in its development, fikih thought undergoes a transformation from taqlid qauli towards taqlid manhaji, from the literalis paradigm to the teleological paradigm. Transformation of thought is realized when the Islamic law as the product of ijtihad was not able to respond to the question of contemporary problems. Negative assumptions that led to it, namely: first, the law understood as a single entity that is not correlation of other entities. Yet in reality, the law is linked with other disciplines, like the social sciences-humanior and natural sciences. Second, the law understood as a final, not in tandem with social development. Third, the law has always been based on a normative-textualis, whereas there are a lot of local knowledge which also carries the philosophical values that are relevant to the purpose of the law. As a solution, integrative approach system needs to be encouraged, given the purpose of human law is to benefit afterlife. Integrative paradigm initiated by Jasser Auda is worthy of consideration in the constellation of ideas and the development of the methodology of ijtihad. By using a systemic approach, Jasser makes maqasid sharia as a philosophical frameworks in the process determination of  law. Law is element of the existing system and closely related to other elements to achieve a goal of Shari'a.